Transforming Ourselves First: The Need of a Paradigm Shift in Peace Research and Peace Education (In Factis Pax: Journal of Peace Education and Social Justice, 2020)
Real Masters (with a capital M) are few, and they are not taken literally or, less diplomatically, they are not taken seriously. Gandhi is no exception. When he meant that the world can only change, if we start changing ourselves, he was inviting all of us to a change, not only the perpetrators of violence.